The Relationship of Mental Health Literacy (MHL) with Psychological Status in Patients with Diabetes Mellitus - Pulmonary Tuberculosis at the Gorontalo City Health Center - Sri Melinda Hippy; Zainuddin; Rachmawaty D. Hunawa (Universitas Muhammadiyah Palu, 2026)
Background: Diabetes Mellitus (DM) and Pulmonary Tuberculosis (Pulmonary TB) are two interrelated chronic diseases that can cause various psychological problems in sufferers. Pulmonary DM-TB patients are at risk of experiencing stress, anxiety, and depression that have an impact on psychological status. One of the factors that is suspected to play a role in this condition is Mental Health Literacy (MHL), which is an individual's ability to understand, recognize, and manage mental health problems. Objective: This study aims to determine the relationship between Mental Health Literacy and psychological status in patients with Diabetes Mellitus–Pulmonary Tuberculosis at the Gorontalo City Health Center. Methods: This study used a quantitative design with a cross-sectional approach. The research population amounted to 75 patients with Pulmonary DM-TB registered in six health centers in the Gorontalo City area. A sample of 63 respondents was selected using the purposive sampling technique. Data were collected using the Mental Health Literacy and psychological status questionnaire, then analyzed using the Chi-Square test with a significance level of 0.05. Results: The results showed that most of the respondents had high Mental Health Literacy as many as 41 respondents (65.1%), while 22 respondents (34.9%) had low Mental Health Literacy. The psychological status of respondents was dominated by the severe distress category of 37 respondents (58.7%) and mild distress as many as 26 respondents (41.3%). The results of the Chi-Square test showed a p-value of 0.006 (p < 0.05), which means that there is a significant relationship between Mental Health Literacy and psychological status in patients with Pulmonary DM-TB. Conclusion: There is a significant relationship between Mental Health Literacy and psychological status in Diabetes Mellitus–Pulmonary Tuberculosis patients at the Gorontalo City Health Center. The better the level of Mental Health Literacy that a patient has, the better their ability to manage psychological conditions during the treatment of chronic diseases.